2017
DOI: 10.1126/science.aal1979
|View full text |Cite
|
Sign up to set email alerts
|

Transition from turbulent to coherent flows in confined three-dimensional active fluids

Abstract: Transport of fluid through a pipe is essential for the operation of macroscale machines and microfluidic devices. Conventional fluids only flow in response to external pressure. We demonstrate that an active isotropic fluid, comprised of microtubules and molecular motors, autonomously flows through meter-long three-dimensional channels. We establish control over the magnitude, velocity profile and direction of the self-organized flows, and correlate these to the structure of the extensile microtubule bundles. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
263
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 275 publications
(279 citation statements)
references
References 65 publications
14
263
0
2
Order By: Relevance
“…, in which self-driven units convert an energy source into useful motion and work, have been the focus of intensive experimental and theoretical studies in recent years and primarily focused on meso-scale or macroscopic fluxes 14 , flocks 15,16 or flows 17,18 from local mechanical forcing. Their use to design nonequilibrium interactions and control self-assembly remains, however, largely unexplored [19][20][21][22] .…”
mentioning
confidence: 99%
“…, in which self-driven units convert an energy source into useful motion and work, have been the focus of intensive experimental and theoretical studies in recent years and primarily focused on meso-scale or macroscopic fluxes 14 , flocks 15,16 or flows 17,18 from local mechanical forcing. Their use to design nonequilibrium interactions and control self-assembly remains, however, largely unexplored [19][20][21][22] .…”
mentioning
confidence: 99%
“…[56][57][58] In general, in vitro studies regularly face the question whether or not they represent the actual biochemical structures and biological functions including their physical properties as seen in vivo. Pioneering genetic, electron microscopy, and live cell imaging studies have identified the cytoskeletal structures in the last decades and paved the way for their subsequent purification.…”
Section: In Vitro Approaches For Energy-driven Molecular Machinesmentioning
confidence: 99%
“…To perform these tasks, cells spatiotemporally coordinate the interactions of force-generating, "active" molecules that create and manipulate non-equilibrium structures and force fields that span up to millimeter length scales [1][2][3]. Experimental active matter systems of biological or synthetic molecules are capable of spontaneously organizing into structures [4,5] and generating global flows [6][7][8][9]. However, these experimental systems lack the spatiotemporal control found in cells, limiting their utility for studying non-equilibrium phenomena and bioinspired engineering.…”
mentioning
confidence: 99%
“…4h) (Video 14). While simplified active matter systems are able to spontaneously generate global flows [6,8], in vivo cytoskeletal-driven fluid flows can be controlled and highly structured [21,22,26].…”
mentioning
confidence: 99%